High-flow nasal cannula vs. non-invasive ventilation in acute hypoxemic respiratory failure: Exporing the role of electrolyte imbalance in patient outcome - Ali Saqlain Haider, Asma Sarwar, Abdul Waheed, Hassan Safdar, Aamir Waseem, Usman Zeeshan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This study investigates the efficacy of high-flow nasal cannula (HFNC) versus non-invasiveventilation (NIV) in managing acute hypoxemic respiratory failure (AHRF), with a particular focus on the impact of electrolyte